Integrating Global Epistemology and Local Action: The OONAR "Local Climate Detectives" Learning Model in Realizing Community Ecological Justice in Elementary Schools - Meirza Nanda Faradita; Ganes Gunansyah; Neni Mariana (Jurnal Penelitian Pendidikan IPA, 2026)
This study proposes a pedagogical model, “Local Climate Detectives,” to integrate global epistemology with students’ local experiences in primary science education. The study addresses the gap between universal scientific knowledge and contextual learning in responding to climate change challenges (SDG 13). A qualitative conceptual approach was employed through a systematic literature review, guided by Robertson’s Glocalization framework. The analysis focused on the mechanisms of interpenetration and mutual shaping between global and local knowledge systems. The result of this study is a theoretical construction of the OONAR learning model (Orientation–Observation–Negotiation–Action–Reflection) as an operational framework for glocal learning. Within this model, the Correlation Reasoning stage is positioned as a key epistemic process that connects locally generated data (e.g., environmental observations) with global scientific references. This integration is designed to foster resilient ecological reasoning and support collective decision-making grounded in local socio-cultural values. The study concludes that the proposed model provides a coherent framework for developing students’ climate literacy and glocal identity, positioning them as active contributors to community-based ecological justice.